Disease burden, cost modelling and the AIDS funding debate-towards clarity on whether the world is spending 'too much' on HIV/AIDS - MacDevette, Matthew (School of Economics, 2015)
With pressures from the recent financial crisis forcing donors to carefully review their spending priorities, some have claimed, firstly, that HIV/AIDS receives too much money relative to its disease burden and, secondly, that the future costs of treating those with the disease will become unmanageable. This paper seeks to clarify each of these two areas...